Positive electrode sheet for solid-state battery, method for manufacturing same, solid-state battery, and electric device
Patent Information
- Application Number
- CN202611223914.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
AI Technical Summary
但是由于现有工艺限制电解质层的面密度一般要20 mg/cm2,该方法引入电解质层,会直接增加电芯厚度、质量与制造成本,降低活性材料占比,进而拉低电池的体积与质量能量密度,削弱其性能优势,成为商业化的重要阻碍
本发明通过在正极活性层表面构建一层特定厚度的氟化钝化层,该钝化层由涂覆料的原位成分经氟化转化而来,具有以下技术效果:
Smart Images

Figure CN123017875A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to the positive electrode sheet of a solid-state battery and its preparation method, as well as solid-state batteries and electrical devices. Background Technology
[0002] Lithium-ion batteries are now widely used in various applications, and are particularly crucial in portable electronic devices and electric vehicles. Today, market demand for batteries with high power, high energy density, and improved safety continues to rise, with the electric vehicle industry being especially eager to meet this need. Against this backdrop, solid-state batteries have emerged as the most promising next-generation technology compared to traditional lithium-ion batteries. A key advantage of solid-state batteries is that the solid electrolyte can be adapted to use metallic lithium (or lithium alloys) as the negative electrode material. This technological innovation can increase the volumetric energy density of batteries by up to 70% and the gravimetric energy density by up to 40%.
[0003] To achieve the goal of commercializing solid-state batteries, the research community is increasingly adopting a dual-electrolyte system design, which combines multiple solid-state electrolytes within a single cell and combines them based on their respective performance advantages. One highly promising combination scheme is to use a sulfide electrolyte as the membrane electrolyte (which has high ionic conductivity) and a halide oxide electrolyte (which has excellent oxidation resistance) in the positive electrode region.
[0004] Scientific research has found that when sulfide electrolytes and halide oxide electrolytes come into contact near the positive electrode active material, a three-phase interface forms, which exhibits inherent instability during battery cycling. This interfacial instability is unrelated to the specific chemical composition of the halide oxide electrolyte and can exacerbate battery performance degradation, induce sulfur-based gas evolution, and cause rapid performance decline. Such problems caused by the three-phase interface are common in other dual-electrolyte systems and may hinder the practical application of dual-electrolyte solid-state batteries. Ultimately, overcoming the challenge of three-phase interface degradation is crucial to propelling dual-electrolyte solid-state batteries from laboratory research to industrial application.
[0005] A paper titled "Triple-phase boundary instability as a key degradation factor in sulfide|(oxy)halide dual-electrolyte solid-state batteries" presents a method for adding a halide oxide solid electrolyte layer between the sulfide solid electrolyte layer and the positive electrode. This method can isolate the positive electrode-halide oxide from the sulfide, avoiding the formation of a sulfide-halide-active material three-phase interface that affects battery performance. However, due to current process limitations, the areal density of the electrolyte layer is generally required to be 20 mg / cm³. 2This method introduces an electrolyte layer, which directly increases the cell thickness, mass, and manufacturing cost, reduces the proportion of active materials, and consequently lowers the volume and mass energy density of the battery, weakening its performance advantages and becoming a major obstacle to commercialization.
[0006] In view of this, the present invention is proposed. Summary of the Invention
[0007] The purpose of this invention is to provide a positive electrode sheet for a solid-state battery and a method for preparing the same, as well as a solid-state battery and an electrical device thereon, in order to improve at least one of the problems mentioned in the background art.
[0008] This invention is implemented as follows: In a first aspect, the present invention provides a positive electrode sheet for a solid-state battery, comprising a positive current collector and a positive active layer disposed on the positive current collector; The positive electrode active layer includes an unfluorinated layer and a fluorinated passivation layer formed on the surface of the unfluorinated layer; The unfluorinated layer includes a coating material, which includes a positive electrode active material and a chloride solid electrolyte; the fluorinated passivation layer includes a fluorinated coating material, wherein the mass percentage of F in the fluorinated passivation layer is 0.3%~2%, and the thickness of the fluorinated passivation layer is 20~120 nm.
[0009] In an optional embodiment, the coating material comprises 50-85 wt% positive electrode active material, 10-45 wt% chloride solid electrolyte, 0.5-4 wt% conductive agent and 0.3-3 wt% binder; Optionally, the positive electrode active material is a ternary positive electrode material; Optionally, the ternary cathode material is a nickel-cobalt-manganese ternary cathode material or a nickel-cobalt-aluminum ternary cathode material.
[0010] In an optional embodiment, the chloride solid electrolyte is selected from one or more of Li3InCl6, Li3YCl6, Li2ZrCl6, Li3ScCl6, Li3YBr6, Li2HfCl6, Li2ZrOCl4, LiNbOCl4, LiTaOCl4 and Li3OCl; And / or, the conductive agent is selected from one or more of carbon black, vapor-grown carbon fiber, single-arm carbon nanotube and multi-wall carbon nanotube; And / or, the adhesive is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyethylene oxide, polypropylene, polyethylene, nitrile rubber, polypropylene carbonate, polyamide, styrene-butadiene rubber and polyacrylic acid.
[0011] In an optional embodiment, the thickness of the fluorinated passivation layer is 40~60 nm.
[0012] In a second aspect, the present invention provides a method for preparing a positive electrode sheet of a solid-state battery as described in any of the foregoing embodiments, comprising: A positive electrode blank is provided, the positive electrode blank comprising a positive current collector and an active coating disposed on the surface of the positive current collector, the active coating being formed by the coating material; The positive electrode blank is placed in a vacuum chamber for fluorination treatment. The fluorination treatment includes introducing fluorine source gas into the vacuum chamber, turning on the plasma power supply to ionize the fluorine source gas to generate fluorine plasma, and bombarding the surface of the active coating with fluorine plasma to form a fluorinated passivation layer.
[0013] In an optional embodiment, the fluorine source gas is selected from one or more of nitrogen trifluoride, carbon tetrafluoride, sulfur hexafluoride, and pure fluorine gas.
[0014] In an optional embodiment, during the fluorination process, the cavity vacuum is controlled at 5~45Pa; the discharge power is set to 80~150W; the gas flow rate is stabilized at 20~50sccm; and the fluorination time is 5~15min. Optionally, the fluorination time is 8 to 12 minutes.
[0015] In an optional embodiment, after fluorination, the positive electrode sheet after fluorination is further subjected to constant temperature treatment at a temperature of 40~60°C for a time of 5~120 minutes.
[0016] Thirdly, the present invention provides a solid-state battery, comprising a positive electrode, a sulfide solid electrolyte membrane, and a negative electrode arranged sequentially as described in any of the foregoing embodiments.
[0017] Fourthly, the present invention provides an electrical device including a solid-state battery as described in the foregoing embodiments.
[0018] The present invention has the following beneficial effects: This invention constructs a fluorinated passivation layer of a specific thickness on the surface of the positive electrode active layer. This passivation layer is derived from the in-situ components of the coating material through fluorination conversion, and has the following technical advantages: Interface stabilization: The fluorinated passivation layer acts as a physical barrier, effectively isolating the internal chloride solid electrolyte from direct contact with the external environment (such as moisture and sulfide solid electrolyte), significantly improving the environmental stability of the electrode. Furthermore, it prevents direct contact between the external sulfide solid electrolyte and the positive electrode active material during charge and discharge, suppressing interfacial side reactions and reducing interfacial impedance.
[0019] Without reducing energy density: The passivation layer is derived from the in-situ components of the coating material through fluorination. It does not introduce additional layer structures, but only forms a functional passivation layer through the reconstruction of surface chemical bonds. It does not increase the coating thickness or weight, and does not encroach on the internal space of the cell or the filling capacity of the positive electrode active material.
[0020] Ion transport and structural integrity: By controlling the passivation layer thickness to 20-120 nm, effective physical isolation is ensured while avoiding the obstruction of lithium-ion transport due to excessive passivation layer thickness. This thickness range ensures that the rate performance of the battery is not significantly affected, while maintaining the structural integrity of the passivation layer during cycling, making it less prone to breakage.
[0021] Tight interface contact: Since the fluorinated passivation layer is generated in situ by surface treatment of the positive electrode active layer itself, it has an integrated structure with the internal unfluorinated layer with a gradual change in composition, avoiding the introduction of additional interfaces and ensuring extremely low interface resistance and excellent mechanical bonding. Attached Figure Description
[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a schematic diagram of the structure of the positive electrode sheet provided in an embodiment of the present invention; Figure 2 This is a first assembly flowchart of a solid-state battery provided in an embodiment of the present invention; Figure 3 This is a second assembly flowchart of a solid-state battery provided in an embodiment of the present invention; Figure 4 This is a schematic diagram of an example of an electrical device provided in an embodiment of the present invention. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0025] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0026] In response to a series of problems with existing technologies, the inventors considered the following: (1) Sulfide solid electrolytes are not resistant to high voltage on the positive electrode side: Because sulfide solid electrolytes have a narrow intrinsic thermodynamic stability window, the sulfur and phosphorus elements in their framework are easily oxidized at high potentials, generating insulating byproducts and sulfur-based gases. Simultaneously, high-valence metal ions on the high-voltage cathode surface catalyze electrolyte decomposition, further reducing the activation energy. During cycling, factors such as interfacial stress, local potential overshoot, and electron leakage exacerbate side reactions, creating a vicious cycle of increased impedance and performance degradation, ultimately limiting their direct application in high-voltage systems.
[0027] (2) Reasons and disadvantages for using halide oxide electrolytes instead of sulfide solid electrolytes on the positive electrode side: Halide electrolytes possess a wider electrochemical stability window, with an upper oxidation potential of up to 4.2 V (vs. Li). + Its conductivity (0.5-10 mS / cm) is significantly higher than that of sulfide electrolytes, far exceeding the intrinsic oxidation stability limit of 2.5-3.0 V. This allows for direct compatibility with high-voltage ternary and lithium-rich manganese-based cathode materials, avoiding the decomposition of sulfides, the evolution of sulfur-based gases, and increased interfacial impedance at high potentials. Furthermore, its ionic conductivity (0.5-10 mS / cm) meets the transport requirements of cathode composite systems. However, halide electrolytes still have significant drawbacks: First, their interfacial stability with lithium metal / lithium alloy anodes is insufficient, making them prone to reduction and decomposition, thus preventing direct use as membrane electrolytes. Second, they form a three-phase interface upon contact with sulfide electrolytes, leading to spontaneous reactions during cycling and causing interface degradation and performance decline. Third, some halide electrolytes are sensitive to moisture, requiring stringent synthesis and storage conditions, and have high raw material costs, hindering their large-scale application.
[0028] (3) Add a halide oxide solid electrolyte layer between the sulfide solid electrolyte layer and the positive electrode: To address the interfacial stability challenge of sulfide solid electrolytes on the high-voltage positive electrode side, a common engineering approach is to introduce a halide oxide solid electrolyte buffer layer between the sulfide solid electrolyte membrane and the positive electrode. The core idea of this approach is to utilize the high voltage of halide oxide electrolytes (up to 4.2 V vs. Li) to achieve this. +The high oxidation stability of halogenated oxides (H₂O / Li) allows for direct contact with the high-voltage cathode active material, thus isolating the sulfide electrolyte from direct contact with the cathode and preventing oxidative decomposition of sulfides at high potentials. Simultaneously, this design avoids the formation of a thermodynamically unstable three-phase boundary at the interface between sulfides, halides, and the cathode active material, preventing spontaneous side reactions, gas generation, and high-resistivity byproducts during cycling, thereby ensuring battery cycle life and rate performance. However, due to limitations in current solid-state battery fabrication processes such as dry electrodes and cold pressing, the areal density of the halide oxide buffer layer typically needs to reach 20 mg / cm² to achieve continuous and dense interface coverage, which presents a series of commercialization bottlenecks. Specifically: First, the additional buffer layer directly increases the overall thickness of the cell and the mass of inactive components, driving up material and manufacturing costs; second, the introduction of the buffer layer reduces the space available for active materials within the cell, resulting in a significant decrease in the volumetric energy density and gravimetric energy density of the battery, weakening the core performance advantages of solid-state batteries compared to traditional lithium-ion batteries; finally, process issues such as interface contact and stress matching between different electrolyte layers will further affect the long-term stability of the battery, becoming a key obstacle restricting the large-scale industrial application of this solution.
[0029] Based on the above considerations, the technical solution of this invention is proposed as follows: like Figure 1 As shown, an embodiment of the present invention provides a positive electrode sheet for a solid-state battery, comprising a positive electrode current collector and a positive electrode active layer disposed on the positive electrode current collector; The positive electrode active layer includes an unfluorinated layer and a fluorinated passivation layer formed on the surface of the unfluorinated layer; The unfluorinated layer includes a coating material, which includes a positive electrode active material and a chloride solid electrolyte; the fluorinated passivation layer includes a fluorinated coating material, wherein the mass percentage of F in the fluorinated passivation layer is 0.3% to 2% (e.g., 0.3%, 0.5%, 0.8%, 1%, 1.5% or 2%, or any value within the range of any two of the aforementioned values, optionally 0.3% to 1.5%), and the thickness of the fluorinated passivation layer is 20 to 120 nm (e.g., 20 nm, 40 nm, 50 nm, 70 nm, 80 nm, 100 nm or 120 nm, or any value within the range of any two of the aforementioned values).
[0030] This invention constructs a fluorinated passivation layer of a specific thickness on the surface of the positive electrode active layer. This passivation layer is derived from the same in-situ composition as the unfluorinated layer through fluorination conversion, and has the following technical advantages: Interface stabilization: The fluorinated passivation layer acts as a physical barrier, effectively isolating the internal chloride solid electrolyte from direct contact with the external environment (such as moisture and sulfide solid electrolyte), significantly improving the environmental stability of the electrode. Furthermore, it prevents direct contact between the external sulfide solid electrolyte and the positive electrode active material during charge and discharge, suppressing interfacial side reactions and reducing interfacial impedance.
[0031] Without reducing energy density: The passivation layer is derived from the in-situ components of the coating material through fluorination. It does not introduce additional layer structures, but only forms a functional passivation layer through the reconstruction of surface chemical bonds. It does not increase the coating thickness or weight, and does not encroach on the internal space of the cell or the filling capacity of the positive electrode active material.
[0032] Ion transport and structural integrity: By controlling the passivation layer thickness to 20-120 nm, effective physical isolation is ensured while avoiding the obstruction of lithium-ion transport due to excessive passivation layer thickness. This thickness range ensures that the rate performance of the battery is not significantly affected, while maintaining the structural integrity of the passivation layer during cycling, making it less prone to breakage.
[0033] Tight interface contact: Since the fluorinated passivation layer is generated in situ by surface treatment of the positive electrode active layer itself, it has an integrated structure with the internal unfluorinated layer with a gradual change in composition, avoiding the introduction of additional interfaces and ensuring extremely low interface resistance and excellent mechanical bonding.
[0034] Furthermore, in some embodiments of the present invention, the coating material comprises 50-85 wt% (e.g., 50 wt%, 60 wt%, 70 wt%, 80 wt%, or 85 wt%, or any value within the range of any two of the aforementioned values) of positive electrode active material, 10-45 wt% (e.g., 10 wt%, 20 wt%, 30 wt%, 40 wt%, or 45 wt%, or any value within the range of any two of the aforementioned values) of chloride solid electrolyte, 0.5-4 wt% (e.g., 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, or 4 wt%, or any value within the range of any two of the aforementioned values) of conductive agent, and 0.3-3 wt% (e.g., 0.3 wt%, 1 wt%, 2 wt%, or 3 wt%, or any value within the range of any two of the aforementioned values) of binder.
[0035] The high content of positive electrode active material (50-85 wt%) provides an ample ion supply for the electrode, effectively ensuring the high energy density and high capacity of the battery. Secondly, the 10-45 wt% chloride solid electrolyte constructs a highly efficient ion transport network within the active layer. Its high room-temperature ionic conductivity and good mechanical ductility not only ensure rapid ion migration between positive electrode particles, thereby improving the battery's rate performance and power density, but also adapt to the volume changes of the positive electrode material through plastic deformation during charge and discharge, maintaining tight solid-solid contact with the active material particles, significantly improving cycle stability and lifespan. Simultaneously, the 0.5-4 wt% conductive agent forms a highly efficient electron percolation network within the active layer. While ensuring rapid electron transport, it avoids side reactions or a decrease in volumetric energy density caused by excessive carbon material, achieving a balance in ion-electron transport. Furthermore, the 0.3-3 wt% binder provides the necessary mechanical cohesion and adhesion to the current collector for the active layer, ensuring the structural integrity and flexibility of the electrode during fabrication, while minimizing obstacles to ion transport and dilution of energy density. After fluorination, the aforementioned components form chemical bonds such as In-F, Zr-F, and Li-F on the surface of the halide solid electrolyte, and stronger transition metal-F covalent bonds form on the surface of the ternary cathode particles, anchoring the lattice transition metal. The fluoride layer and the cathode substrate are atomically bonded with strong adhesion; the fluoride layer is not easily peeled off during charge-discharge cycles when interfacial stress occurs. Solid-state batteries using sulfide solid electrolytes as electrolyte membranes can provide better electrochemical performance.
[0036] Furthermore, in some embodiments of the present invention, the positive electrode active material is a ternary positive electrode material.
[0037] Optionally, the ternary cathode material can be a nickel-cobalt-manganese ternary cathode material or a nickel-cobalt-aluminum ternary cathode material. Specific examples include NCM911, NCM523, NCM622, NCM811, NCM90.5-6-3.5, NCM95-3-2, NCA, etc.
[0038] Ternary cathode materials, especially high-nickel ternary materials, possess high specific capacity. However, cross-chemical reactions easily occur between transition metals, halide chloride ions, and sulfide sulfide ions at the interface between the ternary cathode, halide electrolyte, and sulfide electrolyte. This generates a large number of high-impedance insulating impurities, leading to severe degradation of the three-phase interface performance. The fluorinated passivation layer solution provided by this invention is particularly effective for these highly active, high-energy-density materials. It can effectively stabilize their surface, suppress side reactions, fully utilize their high capacity advantage, and ensure cycle life.
[0039] Furthermore, in some embodiments of the present invention, the chloride solid electrolyte is selected from one or more of Li3InCl6, Li3YCl6, Li2ZrCl6, Li3ScCl6, Li3YBr6, Li2HfCl6, Li2ZrOCl4, LiNbOCl4, LiTaOCl4 and Li3OCl; And / or, the conductive agent is selected from one or more of carbon black, vapor-grown carbon fiber, single-arm carbon nanotube and multi-wall carbon nanotube; And / or, the adhesive is selected from one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polypropylene (PP), polyethylene (PE), nitrile rubber (NBR), polypropylene carbonate (PPC), polyamide (PA), styrene-butadiene rubber (SBR), and polyacrylic acid (PAA).
[0040] The aforementioned chloride solid electrolytes exhibit high ionic conductivity, but they generally suffer from sensitivity to moisture and poor interfacial stability with high-voltage cathode materials. The fluorinated passivation layer solution provided by this invention offers universal protection for these specific chloride electrolyte systems. Furthermore, the selected conductive agents and binders are commonly used materials in the field, exhibiting good compatibility with the fluorination process, ensuring that the formation of the passivation layer does not affect the internal conductive network and bonding properties of the electrode.
[0041] Furthermore, in some embodiments of the present invention, the thickness of the fluorinated passivation layer is 40~60nm (e.g., 40nm, 45nm, 50nm, 55nm or 60nm, or any value within the range of any two of the aforementioned values).
[0042] The preferred thickness of the fluorinated passivation layer is 40-60 nm, representing a more optimized balance. Within this range, the passivation layer provides more reliable protection, suppresses interfacial side reactions to the greatest extent, and exhibits minimal resistance to lithium-ion transport, which is almost negligible. This results in the battery achieving optimal overall electrochemical performance, namely, excellent cycle stability and rate performance.
[0043] The method for preparing the positive electrode of the solid-state battery provided in this embodiment of the invention includes: A primary positive electrode sheet is provided, comprising a positive current collector and an active coating disposed on the surface of the positive current collector, the active coating being formed by a coating material; The positive electrode blank is placed in a vacuum chamber for fluorination treatment. The fluorination treatment includes introducing fluorine source gas into the vacuum chamber, turning on the plasma power supply to ionize the fluorine source gas to generate fluorine plasma, and bombarding the surface of the active coating with fluorine plasma to form a fluorinated passivation layer.
[0044] This preparation method employs plasma fluorination technology, which offers the following technical advantages: In-situ generation with strong adhesion: By bombarding the surface of the active coating with fluorine plasma, the surface components undergo an in-situ fluorination reaction. The resulting fluorinated passivation layer has no delamination or gaps with the unfluorinated substrate, and the adhesion is far superior to ex-situ methods such as coating or deposition.
[0045] Controllable process and good uniformity: Plasma treatment is a dry process that can form a passivation layer with uniform thickness and consistent composition on the electrode surface by precisely controlling parameters such as power, gas flow rate and time. It has good repeatability and is suitable for large-scale production.
[0046] No high temperature required, protecting the substrate: Plasma bombardment does not require high temperature, avoiding the damage to the structure and performance of the current collector, binder and electrolyte by high temperature treatment.
[0047] It should be noted that other types of passivation treatments can also form a passivation layer, such as nitriding. However, nitriding of the positive electrode active layer surface results in the formation of lithium nitride and transition metal nitrides. Among these, lithium nitride has an oxidation decomposition potential of only 0.44V (vs Li / Li). + The working voltage of the ternary cathode is 3.0–4.3 V, which is much higher than its oxidation threshold. Once the nitrided layer comes into direct contact with the high-potential ternary cathode, it will immediately undergo electrochemical oxidation and decomposition, releasing nitrogen gas and generating insulating lithium oxide impurity phase. The interface impedance will spike sharply, and the passivation protection function will be completely lost. Therefore, fluorination treatment can achieve better interface stability for the surface of the cathode active layer.
[0048] Specifically, the preparation method is as follows: S1. Providing initial products of positive electrode sheets A primary positive electrode material is provided, comprising a positive current collector and an active coating disposed on the surface of the current collector. The primary positive electrode material is prepared into a positive electrode film using dry electrode technology, and then thermally bonded with the current collector to obtain the final product.
[0049] The positive current collector is, for example, carbon-coated aluminum foil, surface-roughened aluminum foil, or porous aluminum foil.
[0050] The active coating is formed by a coating material comprising 50-85 wt% (e.g., 50 wt%, 60 wt%, 70 wt%, 80 wt%, or 85 wt%, or any value within the range of any two of the aforementioned values) of positive electrode active material, 10-45 wt% (e.g., 10 wt%, 20 wt%, 30 wt%, 40 wt%, or 45 wt%, or any value within the range of any two of the aforementioned values) of chloride solid electrolyte, 0.5-4 wt% (e.g., 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, or 4 wt%, or any value within the range of any two of the aforementioned values) of conductive agent, and 0.3-3 wt% (e.g., 0.3 wt%, 1 wt%, 2 wt%, or 3 wt%, or any value within the range of any two of the aforementioned values) of binder.
[0051] S2, Cleaning the surface of the initial positive electrode sheet The initial positive electrode sheet is subjected to dust removal and drying to remove surface dust and solvents, ensuring that the electrode surface is flat and clean, and avoiding impurities from affecting the quality of passivation layer formation.
[0052] S3, fluorinated passivation After surface cleaning, the initial positive electrode sheet is placed in a plasma reaction chamber. The chamber is then evacuated to remove air and moisture, preventing impurities from participating in the reaction and ensuring the purity and stability of the fluorination reaction.
[0053] Fluorine source gas is introduced into the vacuum chamber, and the plasma power supply is turned on. The fluorine source gas is ionized to generate high-energy fluorine plasma that uniformly bombards the positive electrode surface, and a dense fluorinated passivation layer is generated in situ on the material surface through a chemical bonding reaction.
[0054] Optionally, in some embodiments of the present invention, the fluorine source gas is selected from one or more of nitrogen trifluoride, carbon tetrafluoride, sulfur hexafluoride, and pure fluorine gas.
[0055] The gases mentioned above are selected as fluorine sources. They can efficiently ionize to generate active fluorine radicals in a plasma environment. They have high reactivity and can quickly and effectively fluorinate the electrode surface to form a high-quality passivation layer.
[0056] Optionally, in some embodiments of the present invention, during the fluorination process, the cavity vacuum degree is controlled to be 5~45 Pa (e.g., 5 Pa, 15 Pa, 25 Pa, 35 Pa or 45 Pa, or any value within the range of any two of the aforementioned values); the discharge power is set to 80~150 W (e.g., 80 W, 100 W, 120 W, 140 W or 150 W, or any value within the range of any two of the aforementioned values); the gas flow rate is stabilized at 20~50 sccm (e.g., 20 sccm, 30 sccm, 40 sccm or 50 sccm, or any value within the range of any two of the aforementioned values); and the fluorination time is 5~15 min (e.g., 5 min, 8 min, 10 min, 12 min or 15 min, or any value within the range of any two of the aforementioned values). Preferably, the fluorination time is 8 to 12 minutes (e.g., 8 minutes, 9 minutes, 10 minutes, 11 minutes or 12 minutes, or any value within the range of any two of the aforementioned values).
[0057] By controlling the fluorination process parameters (vacuum degree, discharge power, gas flow rate, and time) within the aforementioned specific ranges, the concentration and energy of the fluorine plasma can be precisely controlled, thereby maintaining the growth rate and final thickness of the fluorinated passivation layer within the ideal range (20~120 nm). This avoids over-etching and excessively thick passivation layers due to excessive power or time, and also prevents incomplete passivation layers due to insufficient parameters. The preferred fluorination time of 8~12 min can more stably obtain a passivation layer with the best performance of 40~60 nm thickness.
[0058] S4, Constant Temperature Curing Optionally, in some embodiments of the present invention, after fluorination, the positive electrode sheet after fluorination is further subjected to constant temperature treatment, the constant temperature being 40~60℃ (e.g. 40℃, 45℃, 50℃, 55℃ or 60℃, or any value within the range of any two of the aforementioned points), and the time being 5~120 min (e.g. 5 min, 10 min, 30 min, 60 min, 80 min, 100 min or 120 min, or any value within the range of any two of the aforementioned points).
[0059] Adding a low-temperature isothermal treatment after fluorination helps stabilize the newly formed fluorinated passivation layer, eliminates surface stress or defects that may be generated by plasma bombardment, and makes the structure and composition of the passivation layer more uniform and stable, further improving its protective effect on the electrode and its long-term stability.
[0060] S5, Cooling Encapsulation After the sample has cooled to room temperature naturally, it should be removed, kept dry and isolated from air to prevent the surface passivation layer from becoming damp and failing, thus completing the overall modification process.
[0061] Note: All steps are performed in a dry room with a dew point of <-50 ℃.
[0062] An embodiment of the present invention provides a solid-state battery, which includes a positive electrode, a sulfide solid electrolyte membrane, and a negative electrode arranged sequentially as described in any of the preceding embodiments.
[0063] Solid-state batteries using the positive electrode sheet of this invention exhibit significantly improved cycle life, coulombic efficiency, and rate performance due to the fundamentally improved stability of the positive electrode / electrolyte interface. Simultaneously, the improved electrode environmental stability simplifies the battery assembly process and reduces production costs.
[0064] Solid-state battery assembly methods can be: (1) such as Figure 2 As shown, the electrolyte membrane is combined with the fluorinated positive electrode, and then stacked together with the negative electrode, packaged, and subjected to static pressure treatment; or, (2) as shown Figure 3 As shown, the electrolyte membrane is combined with the negative electrode, and then stacked together with the fluorinated positive electrode, encapsulated, and subjected to static isobaric treatment.
[0065] It should be noted that the reason why the solid-state battery provided by the present invention has a fluorinated passivation layer on the surface of the positive electrode instead of on the surface of the sulfide solid electrolyte membrane is as follows: (1) Sulfide electrolytes have high chemical activity. When the plasma power is too high or the processing time is too long, the high-energy fluorine plasma will etch the electrolyte matrix. Repeated transfer of solid electrolytes increases the exposure time of solid electrolytes in air, destroys the internal lithium-ion transport channels, and causes permanent decay of the electrolyte's ionic conductivity. However, when fluorine plasma acts on the cathode surface, the sulfide electrolyte is not directly bombarded by plasma, avoiding the risk of plasma etching of the electrolyte matrix, and the intrinsic properties of the electrolyte are fully preserved. Halide solid electrolytes and cathode materials have higher tolerance to water vapor, and the performance loss is less when the exposure time is increased.
[0066] (2) During the fluorination process, the chloride in the positive electrode active layer forms atomic-level lattice bonds by replacing the Cl atoms in the lattice with F atoms, making the fluorinated layer more firmly bonded to the substrate; while the LiF obtained by fluorination on the surface of the sulfide electrolyte only accumulates on the electrolyte surface and is attached to the substrate by interfacial bonding, making it more prone to detachment under cyclic stress.
[0067] (3) Surface roughness fluctuations are likely to occur during the preparation of sulfide electrolyte membranes. If the electrolyte surface is uneven, the thickness of the fluorinated layer will vary greatly after plasma bombardment, and side reactions will still occur in the thinner areas. However, if the fluorinated layer is grown on the surface of the positive electrode active layer containing halides, the flatness of the positive electrode coating layer is more controllable, and it is easier to obtain a modified layer with uniform thickness, reducing the probability of modification failure due to defects on the electrolyte membrane surface and reducing the stringent requirements on the polishing process of sulfide electrolyte membranes.
[0068] An embodiment of the present invention provides an electrical device comprising the solid-state battery described above. The solid-state battery can be used as a power source for the electrical device or as an energy storage unit of the electrical device. The electrical device may include mobile devices (typically mobile phones, laptops, etc.), electric vehicles (typically pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, or energy storage systems, etc.
[0069] Figure 4 This is an example of an electrical device. The electrical device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc.
[0070] Example 1 (1) Provide a positive electrode blank, which includes a positive current collector (carbon-coated aluminum foil) and an active coating disposed on the surface of the positive current collector. The positive electrode blank is prepared into a positive electrode film by dry electrode technology and then thermally composited with the current collector. The aluminum foil has a thickness of 12 μm and the active coating has a thickness of 100 μm.
[0071] The positive electrode active layer comprises 75 wt% positive electrode active material, 21.5 wt% chloride solid electrolyte, 3 wt% conductive agent, and 0.5 wt% binder. The positive electrode active material is NCM911, the chloride solid electrolyte is Li3InCl6, the conductive agent is carbon black, and the binder is PVDF.
[0072] (2) The positive electrode sheet is subjected to dust removal and drying treatment to remove surface dust and solvent, ensuring that the electrode surface is flat and clean, and avoiding impurities from affecting the passivation layer forming quality.
[0073] (3) Place the surface-cleaned positive electrode blank into the plasma reaction chamber, vacuum the chamber, remove air and water vapor, prevent heteroatoms from participating in the reaction, and ensure the purity and stability of the fluorination reaction.
[0074] (4) Fluorination treatment: Fluorine source gas is introduced into the vacuum chamber and the plasma power supply is turned on. The fluorine source gas is ionized to generate high-energy fluorine plasma that bombards the positive electrode surface uniformly. A dense fluorinated passivation layer is generated in situ on the material surface through chemical bonding reaction.
[0075] In this step, the fluorine source is nitrogen trifluoride; the chamber vacuum is controlled at 10 Pa; the discharge power is set to 120 W; the gas flow rate is stabilized at 30 sccm; and the fluorination treatment time is 10 min.
[0076] (5) Constant temperature curing treatment: After fluorination, keep the cavity at a constant temperature of 50°C for 60 minutes to allow the surface fluorinated structure to be fully rearranged and cured, thereby improving the density, uniformity and structural stability of the passivation layer and eliminating surface defects.
[0077] (6) Cooling and encapsulation: After the sample has cooled to room temperature naturally, it is taken out and stored in a dry place in the absence of air to prevent the surface passivation layer from getting damp and failing, thus completing the overall modification process.
[0078] Note: All steps are performed in a dry room with a dew point of <-50 ℃.
[0079] The thickness of the fluorinated passivation layer on the surface of the obtained positive electrode is about 50 nm, and the F content is about 0.8 wt%.
[0080] The prepared positive electrode sheet is assembled into a solid-state battery: The negative electrode of the solid-state battery is a silicon-carbon negative electrode (silicon-carbon:LPSC:VGCF:HNBR = 62.5:33.7:1.9:1.9), and the solid electrolyte membrane is a sulfide solid electrolyte (LPSC:HNBR=98:2). LPSC refers to lithium phosphorus sulfur chloride, and HNBR refers to hydrogenated nitrile rubber.
[0081] Example 2 This embodiment is basically the same as embodiment 1, except that: (4) in step, the cavity vacuum degree is controlled to 10Pa; the discharge power is set to 150W, the gas flow rate is stabilized at 25 sccm; and the fluorination treatment time is 10 min.
[0082] The thickness of the fluorinated passivation layer of the prepared positive electrode is about 40 nm, and the F content is about 0.7 wt%.
[0083] Example 3 This embodiment is basically the same as embodiment 1, except that: (4) in step, the cavity vacuum degree is controlled to 15Pa; the discharge power is set to 120W, the gas flow rate is stabilized at 30 sccm; and the fluorination treatment time is 15 min.
[0084] The thickness of the fluorinated passivation layer of the prepared positive electrode is about 60 nm, and the F content is about 1.0 wt%.
[0085] Example 4 This embodiment is basically the same as that of embodiment 1, except that: (4) in step, the vacuum degree of the cavity is controlled to 5Pa; the discharge power is set to 80W; the gas flow rate is stabilized at 20sccm; and the fluorination treatment time is 5min.
[0086] The thickness of the fluorinated passivation layer of the prepared positive electrode is about 20 nm, and the F content is about 0.4 wt%.
[0087] Example 5 This embodiment is basically the same as embodiment 1, except that: (4) the cavity vacuum degree is controlled at 45Pa; the discharge power is set at 150W; the gas flow rate is stabilized at 50sccm; and the fluorination treatment time is 15min.
[0088] The thickness of the fluorinated passivation layer of the prepared positive electrode is about 120 nm, and the F content is about 1.5 wt%.
[0089] Example 6 (1) Provide a positive electrode blank, which includes a positive current collector (aluminum foil) and an active coating disposed on the surface of the positive current collector. The aluminum foil has a thickness of 12 μm and the active coating has a thickness of 100 μm.
[0090] The positive electrode active layer comprises 50 wt% positive electrode active material, 45 wt% chloride solid electrolyte, 4 wt% conductive agent, and 1 wt% binder. The positive electrode active material is NCM523, the chloride solid electrolyte is Li3YCl6, the conductive agent is carbon black, and the binder is PVDF.
[0091] (2) The positive electrode sheet is subjected to dust removal and drying treatment to remove surface dust and solvent, ensuring that the electrode surface is flat and clean, and avoiding impurities from affecting the passivation layer forming quality.
[0092] (3) Place the surface-cleaned positive electrode blank into the plasma reaction chamber, vacuum the chamber, remove air and water vapor, prevent heteroatoms from participating in the reaction, and ensure the purity and stability of the fluorination reaction.
[0093] (4) Fluorination treatment: Fluorine source gas is introduced into the vacuum chamber and the plasma power supply is turned on. The fluorine source gas is ionized to generate high-energy fluorine plasma that bombards the positive electrode surface uniformly. A dense fluorinated passivation layer is generated in situ on the material surface through chemical bonding reaction.
[0094] In this step, the fluorine source is sulfur hexafluoride; the cavity vacuum is controlled at 10 Pa; the discharge power is set to 120 W; the gas flow rate is stabilized at 30 sccm; and the fluorination treatment time is 10 min.
[0095] (5) Constant temperature curing treatment: After fluorination, keep the cavity at a constant temperature of 40°C for 120 minutes to allow the surface fluorinated structure to be fully rearranged and cured, thereby improving the density, uniformity and structural stability of the passivation layer and eliminating surface defects.
[0096] (6) Cooling and encapsulation: After the sample has cooled to room temperature naturally, it is taken out and stored in a dry place in the absence of air to prevent the surface passivation layer from getting damp and failing, thus completing the overall modification process.
[0097] Note: All steps were performed in a dry room with a dew point < -50 °C. The resulting positive electrode surface fluorinated passivation layer was approximately 50 nm thick, with an F content of approximately 0.8 wt%.
[0098] The prepared positive electrode sheet is assembled into a solid-state battery: The negative electrode and solid electrolyte membrane of the solid-state battery are the same as in Example 1.
[0099] Example 7 (1) Provide a positive electrode blank, which includes a positive current collector (aluminum foil) and an active coating disposed on the surface of the positive current collector. The aluminum foil has a thickness of 12 μm and the active coating has a thickness of 100 μm.
[0100] The positive electrode active layer comprises 85 wt% positive electrode active material, 14.2 wt% chloride solid electrolyte, 0.5 wt% conductive agent, and 0.3 wt% binder. The positive electrode active material is NCM622, the chloride solid electrolyte is Li2HfCl6, the conductive agent is carbon black, and the binder is PVDF.
[0101] (2) The positive electrode sheet is subjected to dust removal and drying treatment to remove surface dust and solvent, ensuring that the electrode surface is flat and clean, and avoiding impurities from affecting the passivation layer forming quality.
[0102] (3) Place the surface-cleaned positive electrode blank into the plasma reaction chamber, vacuum the chamber, remove air and water vapor, prevent heteroatoms from participating in the reaction, and ensure the purity and stability of the fluorination reaction.
[0103] (4) Fluorination treatment: Fluorine source gas is introduced into the vacuum chamber and the plasma power supply is turned on. The fluorine source gas is ionized to generate high-energy fluorine plasma that bombards the positive electrode surface uniformly. A dense fluorinated passivation layer is generated in situ on the material surface through chemical bonding reaction.
[0104] In this step, the fluorine source is nitrogen trifluoride; the chamber vacuum is controlled at 10 Pa; the discharge power is set to 120 W; the gas flow rate is stabilized at 30 sccm; and the fluorination treatment time is 10 min.
[0105] (5) Constant temperature curing treatment: After fluorination, keep the cavity at a constant temperature of 60°C for 5 minutes to allow the surface fluorinated structure to be fully rearranged and cured, thereby improving the density, uniformity and structural stability of the passivation layer and eliminating surface defects.
[0106] (6) Cooling and encapsulation: After the sample has cooled to room temperature naturally, it is taken out and stored in a dry place in the absence of air to prevent the surface passivation layer from getting damp and failing, thus completing the overall modification process.
[0107] Note: All steps were performed in a dry room with a dew point < -50 °C. The resulting positive electrode surface fluorinated passivation layer was approximately 50 nm thick, with an F content of approximately 0.8 wt%.
[0108] The prepared positive electrode sheet is assembled into a solid-state battery: The negative electrode and solid electrolyte membrane of the solid-state battery are the same as in Example 1.
[0109] Example 8 (1) Provide a positive electrode blank, which includes a positive current collector (aluminum foil) and an active coating disposed on the surface of the positive current collector. The aluminum foil has a thickness of 12 μm and the active coating has a thickness of 100 μm.
[0110] The positive electrode active layer consists of 83 wt% positive electrode active material, 10 wt% chloride solid electrolyte, 4 wt% conductive agent, and 3 wt% binder. The positive electrode active material is NCA, the chloride solid electrolyte is Li3YCl6, the conductive agent is carbon black, and the binder is PVDF.
[0111] (2) The positive electrode sheet is subjected to dust removal and drying treatment to remove surface dust and solvent, ensuring that the electrode surface is flat and clean, and avoiding impurities from affecting the passivation layer forming quality.
[0112] (3) Place the surface-cleaned positive electrode blank into the plasma reaction chamber, vacuum the chamber, remove air and water vapor, prevent heteroatoms from participating in the reaction, and ensure the purity and stability of the fluorination reaction.
[0113] (4) Fluorination treatment: Fluorine source gas is introduced into the vacuum chamber and the plasma power supply is turned on. The fluorine source gas is ionized to generate high-energy fluorine plasma that bombards the positive electrode surface uniformly. A dense fluorinated passivation layer is generated in situ on the material surface through chemical bonding reaction.
[0114] In this step, the fluorine source is nitrogen trifluoride; the chamber vacuum is controlled at 10 Pa; the discharge power is set to 100 W; the gas flow rate is stabilized at 30 sccm; and the fluorination treatment time is 8 min.
[0115] (5) Constant temperature curing treatment: After fluorination, keep the cavity at a constant temperature of 45°C for 80 minutes to allow the surface fluorinated structure to be fully rearranged and cured, thereby improving the density, uniformity and structural stability of the passivation layer and eliminating surface defects.
[0116] (6) Cooling and encapsulation: After the sample has cooled to room temperature naturally, it is taken out and stored in a dry place in the absence of air to prevent the surface passivation layer from getting damp and failing, thus completing the overall modification process.
[0117] Note: All steps were performed in a dry room with a dew point < -50 °C. The resulting positive electrode surface fluorinated passivation layer was approximately 60 nm thick, with an F content of approximately 0.85 wt%.
[0118] The prepared positive electrode sheet is assembled into a solid-state battery: The negative electrode and solid electrolyte membrane of the solid-state battery are the same as in Example 1.
[0119] Example 9 This embodiment is basically the same as Embodiment 1, except that the discharge power is 60W during the fluorination process. The thickness of the fluorinated passivation layer on the surface of the obtained positive electrode is about 20nm, and the F content is about 0.3wt%.
[0120] Example 10 This embodiment is basically the same as Embodiment 1, except that the discharge power during the fluorination process is 200W. The thickness of the fluorinated passivation layer on the surface of the obtained positive electrode is about 120 nm, and the F content is about 1.4 wt%.
[0121] Comparative Example 1 This comparative example is the initial positive electrode product provided in Example 1, which has not undergone fluorination passivation treatment.
[0122] Assemble the positive electrode into a solid-state battery: The negative electrode and solid electrolyte membrane of the solid-state battery are the same as in Example 1.
[0123] Comparative Example 2 This comparative example is basically the same as Example 1, except that: During the fluorination process, the treatment time was 25 minutes, and the thickness of the fluorinated layer in the resulting positive electrode sheet was 210 nm.
[0124] The prepared positive electrode sheet is assembled into a solid-state battery: The negative electrode and solid electrolyte membrane of the solid-state battery are the same as in Example 1.
[0125] Comparative Example 3 This comparative example is basically the same as Example 1, except that: Replace the fluorine source with nitrogen.
[0126] The prepared positive electrode sheet is assembled into a solid-state battery: The negative electrode and solid electrolyte membrane of the solid-state battery are the same as in Example 1.
[0127] Comparative Example 4 This embodiment provides a solid-state battery, whose positive electrode is the unfluorinated passivated positive electrode of Example 1, and whose solid electrolyte membrane is obtained by fluorination treatment on the positive electrode side of the solid electrolyte membrane of the solid-state battery in Example 1, with the fluorination treatment conditions being the same as those in Example 1.
[0128] Comparative Example 5 This comparative example is basically the same as Example 1, except that the chloride solid electrolyte is replaced with a sulfide solid electrolyte (LPSC).
[0129] Experimental Example The electrochemical performance of the solid-state batteries prepared in each embodiment and comparative example was measured. The specific testing methods were as follows: Under test conditions of 60℃ and 20MPa, the capacitor was first charged to 4.3V at a constant current of 0.1C, and then charged at a constant voltage of 4.3V with a cutoff current of 0.05C. After charging, the capacitor was allowed to stand for 10 minutes. Then it was discharged to 1.5V at a current of 0.1C to obtain the first discharge capacity and first efficiency. The test conditions were 60℃ and 20MPa. First, the voltage was charged to 4.3V at a constant current of 0.5C, and then charged at a constant voltage of 4.3V with a cutoff current of 0.05C. After charging, the voltage was allowed to stand for 10 minutes. Then, the voltage was discharged to 1.5V at a current of 0.5C and cycled for testing.
[0130] Record the test results in Table 1.
[0131] Table 1 Electrochemical performance of each embodiment and comparative example
[0132] As can be seen from Table 1, the solid-state batteries prepared in each embodiment of the present invention have excellent electrochemical performance, which is significantly better than the scheme of Comparative Example 1 that does not perform fluorination passivation treatment on the positive electrode.
[0133] Comparing Examples 9 and 10 with Example 1, it is evident that the cycle stability of both groups of samples is significantly worse. Example 9 has a fluorination power of only 60W, while Example 10 has a fluorination power of 200W. Neither of these fluorination power falls within the preferred range of 80-150W defined in this invention. When the power is too low, the fluorine plasma energy is insufficient, making it difficult to form a continuous and complete fluorinated passivation layer, resulting in numerous defects in interface protection. Conversely, excessively high power will over-etch the ternary lattice and halide electrolyte structure on the cathode surface, exacerbating irreversible side reactions at the interface. This demonstrates that controlling the fluorination power within the 80-150W range ensures a complete and uniform fluorinated passivation layer, effectively improving the battery's cycle stability.
[0134] Comparing Comparative Example 2 with Example 1, it can be seen that the specific capacity, coulombic efficiency, and capacity retention rate of the battery in Comparative Example 2 are significantly degraded in the first cycle. The thickness of its fluorinated passivation layer reaches 210 nm, which exceeds the 20~120 nm limit of this invention. An excessively thick passivation layer will significantly increase the lithium-ion interface transport resistance, hinder charge migration, and increase interface polarization loss, resulting in a simultaneous decrease in battery rate performance and cycle life.
[0135] Comparing Comparative Example 3 with Example 1, it can be seen that the electrochemical indicators of the battery treated with nitrogen plasma nitriding are significantly worse. The electrochemical decomposition potential of the lithium nitride generated after nitriding is only 0.44V, which is far lower than the working voltage range of 3.0~4.3V of the ternary cathode. Under high voltage, the nitriding layer decomposes and fails rapidly, and cannot stably block the interdiffusion of ions at the interface of the ternary, halide and sulfide phases. This fully demonstrates that the interface stabilization effect of fluorination modification is far better than that of nitriding modification.
[0136] Comparing Comparative Example 4 with Example 1, it can be seen that the battery with only fluorination of the sulfide solid electrolyte membrane and no modification of the positive electrode active layer has poor overall performance. The sulfide electrolyte matrix is easily damaged by fluorine plasma etching, and the LiF passivation layer formed on its surface is only a surface attachment structure, which is prone to falling off and failing under cyclic stress. In contrast, the present invention performs in-situ fluorination on the surface of the halide-containing positive electrode, and F atoms can replace Cl atoms in the halide lattice to form an atomically bonded passivation layer, resulting in better interfacial bonding strength and long-term barrier effect.
[0137] Comparing Comparative Example 5 with Example 1, it can be seen that the electrochemical performance of the battery without the addition of chloride solid electrolyte to the positive electrode active layer is significantly reduced; the unstable interface between the sulfide solid electrolyte and the positive electrode material leads to poor battery cycle performance.
[0138] In summary, the solid-state battery cathode provided by the embodiments of the present invention has the following technical advantages by constructing a fluorinated passivation layer of a specific thickness on the surface of the cathode active layer. This passivation layer is derived from the in-situ components of the coating material through fluorination conversion: (1) Based on the in-situ bonding passivation feature, the interface side reaction is suppressed for a long time, and the cycle stability is greatly improved. Differentiated technical features: The present invention realizes the chemical bond reconstruction of the solid battery cathode through high-energy bombardment of fluorine plasma, and generates a fluorinated passivation layer that is tightly bonded to the substrate in situ. There are no gaps between the layers and it is not easy to fall off. The existing technology adopts the method of physically stacking halide oxide buffer layers, which only relies on physical bonding to achieve interface isolation. The interlayer bonding force is weak, and cracking, peeling and failure problems are easy to occur during cycling.
[0139] (2) Based on the high ion conductivity of thin layers, the interfacial impedance is significantly reduced and the rate performance is optimized. The present invention can precisely control the formation of 20~120nm nanoscale ultrathin fluorinated passivation layers. The passivation layers have both excellent ion conductivity and electronic insulation, no interfacial barrier defects, and do not affect lithium ion transport. The existing technology stacked halide buffer layers are micron-thick layers with high ion conduction resistance and gaps in interlayer bonding, which easily generate additional interfacial impedance and seriously affect charge transport efficiency.
[0140] (3) Based on the feature of no additional coating, the problem of reduced energy density is completely solved. The present invention is an in-situ modification process of the positive electrode surface, which forms a functional passivation layer only by reconstructing the surface chemical bonds. It does not add any coating thickness or weight, and does not occupy the internal space of the cell or the filling capacity of the positive electrode active material. The existing technology requires additional deposition and stacking of micron-level halide oxide buffer layers, which inevitably increases the overall thickness and weight of the cell, occupies the filling space of the positive electrode active material, and causes an irreversible reduction in energy density.
[0141] (4) Based on the inert protective characteristics of fluorination, the electrolyte's environmental tolerance is improved and production losses are reduced. The fluorinated passivation layer generated by this invention has extremely strong chemical inertness and a dense and uniform structure. It can form a complete protective barrier on the surface of the positive electrode of the solid-state battery, effectively isolating it from air and moisture corrosion. The surface of the unmodified positive electrode and the electrolyte modified by the traditional buffer layer do not have a dense inert protective structure. The sulfide and halide components are very easy to react with water and oxygen in the air, causing electrolyte failure and performance degradation.
[0142] Therefore, solid-state batteries containing the positive electrode provided by this invention also have excellent electrochemical performance.
[0143] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A positive electrode sheet for a solid-state battery, characterized in that, It includes a positive current collector and a positive active layer disposed on the positive current collector; The positive electrode active layer includes an unfluorinated layer and a fluorinated passivation layer formed on the surface of the unfluorinated layer; The unfluorinated layer includes a coating material, which includes a positive electrode active material and a chloride solid electrolyte; the fluorinated passivation layer includes a fluorinated coating material, wherein the mass percentage of F in the fluorinated passivation layer is 0.3% to 2%, and the thickness of the fluorinated passivation layer is 20 to 120 nm.
2. The positive electrode of the solid-state battery according to claim 1, characterized in that, The coating material comprises 50-85 wt% positive electrode active material, 10-45 wt% chloride solid electrolyte, 0.5-4 wt% conductive agent and 0.3-3 wt% binder; Optionally, the positive electrode active material is a ternary positive electrode material; Optionally, the ternary cathode material is a nickel-cobalt-manganese ternary cathode material or a nickel-cobalt-aluminum ternary cathode material.
3. The positive electrode of the solid-state battery according to claim 2, characterized in that, The chloride solid electrolyte is selected from one or more of Li3InCl6, Li3YCl6, Li2ZrCl6, Li3ScCl6, Li3YBr6, Li2HfCl6, Li2ZrOCl4, LiNbOCl4, LiTaOCl4 and Li3OCl; And / or, the conductive agent is selected from one or more of carbon black, vapor-grown carbon fiber, single-arm carbon nanotubes, and multi-wall carbon nanotubes; And / or, the adhesive is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyethylene oxide, polypropylene, polyethylene, nitrile rubber, polypropylene carbonate, polyamide, styrene-butadiene rubber, and polyacrylic acid.
4. The positive electrode of the solid-state battery according to any one of claims 1 to 3, characterized in that, The thickness of the fluorinated passivation layer is 40~60nm.
5. A method for preparing a positive electrode sheet for a solid-state battery as described in any one of claims 1 to 4, characterized in that, include: A positive electrode blank is provided, the positive electrode blank comprising a positive current collector and an active coating disposed on the surface of the positive current collector, the active coating being formed by the coating material; The positive electrode blank is placed in a vacuum chamber for fluorination treatment. The fluorination treatment includes introducing fluorine source gas into the vacuum chamber, turning on the plasma power supply to ionize the fluorine source gas to generate fluorine plasma, and bombarding the surface of the active coating with the fluorine plasma to form the fluorinated passivation layer.
6. The preparation method according to claim 5, characterized in that, The fluorine source gas is selected from one or more of nitrogen trifluoride, carbon tetrafluoride, sulfur hexafluoride, and pure fluorine gas.
7. The preparation method according to claim 5, characterized in that, During fluorination, the chamber vacuum level is controlled at 5~45Pa; the discharge power is set at 80~150W; the gas flow rate is stabilized at 20~50sccm; and the fluorination time is 5~15min. Optionally, the fluorination time is 8 to 12 minutes.
8. The preparation method according to claim 5, characterized in that, The fluorination process further includes subjecting the fluorinated positive electrode to a constant temperature treatment at 40-60°C for 5-120 minutes.
9. A solid-state battery, characterized in that, It includes a positive electrode, a sulfide solid electrolyte membrane, and a negative electrode, arranged sequentially as described in any one of claims 1 to 4.
10. An electrical device, characterized in that, Including the solid-state battery as described in claim 9.
